Optimization of Marriage Registration as Legal Certainty of Children's Rights in the Perspective of Maqasid Shariah - Mohamad Kasim, Nur; Nanang M. Kamba, Sri; ., Zakiyah; Karim, Fibriyanti (KnE Social Sciences, 2022)
Problems in the household are always related to children. Children are the most significant mandate from Allah SWT. They must be cared for and protected even if they get into legal problems. Marriage registration is a form of legal certainty for children’s rights. Often children do not get the fulfillment of their rights due to the actions of their parents. The rise of unregistered marriages is one of the reasons why the legal certainty of children’s rights is questioned. The legal consequences of unregistered marriages create new problems for children, incredibly fulfilling their rights. Therefore, it is necessary to optimize the registration of this marriage for the future of the family, especially the children. Of course, optimizing marriage registration is inseparable from the participation of related parties. It requires synergy between the government, the Office of Religious Affairs (KUA), the Population and Civil Registration Service (DISDUKCAPIL), and the community. Marriage registration is essential, especially from the legal aspect, both in positive and Islamic law. Because basically, Islamic law does not oblige every marriage contract, but marriage registration is essential from the point of view of its benefits. This research belongs to empirical juridical research, using primary, secondary, and tertiary data collection techniques. This study uses a case approach and data analysis techniques used descriptively. The results of the discussion in this study found that marriage registration is beneficial for couples in terms of Islamic law and positive law; not just administration but providing legal certainty to wives, especially children born in terms of child status, education, and inheritance rights. Gorontalo Province marriage registration by the KUA and Disdukcapil has been running optimally even though the data found in unregistered marriages are pretty high, and this is because people do not understand the importance of marriage registration. Keywords: optimization, marriage registration, legal certainty, Maqasid Shariah